Designing a Cloud-based OBE curriculum evaluation system: A multidimensional requirements model for Islamic higher education - Khaeroni Khaeroni; Sabri Sabri; Mira Mira (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2026)
The implementation of Outcome-Based Education (OBE) requires curriculum evaluation systems capable of monitoring learning outcomes systematically, transparently, and continuously. However, curriculum evaluation in many Islamic higher education institutions remains fragmented, relying on disconnected spreadsheets, paper-based documentation, and isolated academic information systems that hinder evidence-based quality assurance and accreditation processes. This study aims to identify the system requirements for a cloud-based OBE curriculum evaluation system that supports effective governance, constructive alignment, and stakeholder engagement. A development-oriented mixed-methods design employing a convergent parallel approach was adopted. Data were collected from study program leaders, lecturers, quality assurance personnel, students, alumni, and industry representatives through interviews, observations, document analysis, and questionnaires. Qualitative data were analyzed thematically, while quantitative data were examined using descriptive statistics to prioritize system requirements. The findings reveal four interrelated dimensions of system requirements: managerial, technical, pedagogical, and stakeholder integration. Stakeholders emphasized the need for centralized CPL–CPMK databases, cloud-native architecture with API integration, automated OBE mapping and learning analytics, digital assessment repositories, student e-portfolios, and stakeholder portals supporting tracer studies and competency gap analysis. Based on these findings, the study proposes a four-dimensional cloud-based system requirements model that integrates governance, digital infrastructure, pedagogy, and stakeholder participation. The proposed model provides a conceptual foundation for developing scalable curriculum evaluation systems that strengthen quality assurance, accreditation readiness, and graduate relevance in Islamic higher education.